SINERGI PEMBERDAYAAN WARGA DALAM MEWUJUDKAN LINGKUNGAN HIJAU DAN SEHAT - Aji, Gatot Bintoro Putra (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research examines the synergy of citizen empowerment in creating a green and healthy environment through a case study in Kota Baru Village, Tanjung Karang Timur District. The main focus of the research is how active community participation, collaboration with the village government, and support from various parties can encourage the creation of a more beautiful, healthy, and sustainable environment. The implemented programs include planting trees in open spaces, creating biopore infiltration holes for flood control and organic waste processing, and promoting a clean and healthy lifestyle. The research method used a descriptive qualitative approach, collecting data through field observations, interviews, and activity documentation. The results show that citizen involvement through mutual cooperation not only improves the quality of the physical environment but also strengthens social bonds between residents and fosters a sense of ownership of shared living spaces. Furthermore, environmental empowerment activities have a positive impact on public health by reducing waste, improving air quality, and creating green spaces that can be used for social activities. In conclusion, the synergy of citizen empowerment is key to the success of sustainable environmental development at the local level and can serve as a model for replication in other urban areas.